Changes of EU Industrial Policy and its Effects on Romania’s Industrial Paradigm - Voica, Marian Catalin (Industrija, 2017)
Latest developments on the international markets create new challenges for the old way of industrial production and development. As the developing countries take the share of important players from the EU it is more and more visible the need for a change of the industrial policy. The advance in technology and the way we produce goods it’s changing and the need for more advanced and more customized products is growing. The idea that there is no need for industrial policy and the believe that the market must be felt free is also loosing supporters in front of new actors from countries with a strong targeted industrial policy which get higher and higher market shares.
Keywords: Europe 2020; growth; development; Industries; Industrial Policy